Pengaruh Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Di PT Krakatau Bandar Samudra - Rifaldi Maniku; Hany Azza Umama; Muhammad Nurhaula Huddin (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to determine the effect of leadership and work discipline on employee performance conducted at PT Krakatau Bandar Samudra. The population in this study amounted to 256 people. The sampling technique used was random sampling and the number of samples was calculated using the Slovin formula so that the total sample was 72 employees. Data collected by observation and questionnaire. The analytical tool used is multiple linear regression analysis, to test the hypothesis used the t test and f test.Hypothesis testing results show that leadership has a significant effect on employee performance. Work discipline on employee performance has no significant effect. Leadership and work discipline together have a significant effect on employee performance.